Pengaruh Penambahan Ampas Kopi pada Tanah Lempung Terhadap Daya Dukung Tanah - Leonard Zeth Karurukan; Irwan Lie Keng Wong; Pebrinar Sangle (Paulus Civil Engineering Journal, 2022)
Clay soils contain a soil with a certain particle mineral content where there are sand or silt particles, there is also organic matter that is the material for sussunnyz. This type of soil is poor in terms of soil carrying capacity where the condition of the soil does not allow for road construction to be built on it. It is necessary to make efforts to improve the condition of the soil in order to increase its carrying capacity and soil stabilization is one of the options in increasing the carrying capacity of the soil. Soil samples were taken from Lambanan village, Mamasa District, Mamasa Regency and then the original soil contch was mixed with coffee grounds at variations of 5%, 10%, and 15%. The experiments carried out in the laboratory are soil moisture content, Atterberg boundary, soil specific gravity, soil encroachment and CBR. The CBR test showed an increase in the percentage value of CBR. The change in soil carrying capacity occurred in the addition of 10% of coffee grounds, from 1.73% before the addition rose to 3.8% there was an increase in CBR of 1.33%. On the addition of the pulp of the header: 15% CBR value. to 4.415% there was an increase in CBR of 1.708%. In this study, it was seen that the addition of coffee grounds to clay soils can increase the value of the CBR number and soil power